Inflation, Faetor Substitution and Growth - Rainer Klump (Kredit und Kapital, 2005)
Inflation, Faktorsubstitution und Wirtschaftswachstum Jüngere empirische Studien über den Zusammenhang zwischen Inflation und Wachstum zeigen, dass Inflation auch schon bei relativ geringen Raten negative Wachstumseffekte besitzen kann. In der monetären Wachstumstheorie fehlt es jedoch an Erklärungen dafür. Wie im vorliegenden Beitrag gezeigt wird, können die negativen Wachstumseffekte von Inflation unter Rückgriff auf inflationsbedingte Veränderungen der gesamtwirtschaftlichen Substitutionselastizität erklärt werden. In einem einfachen Modell der monetären neoklassischen Wachstumstheorie lässt sich nachweisen, dass dieser Effekt normalerweise groß genug ist, um mögliche positive Wachstumseffekte der Inflation zu dominieren. – – Recent empirical studies on the inflation-growth-relationship underline that inflation has negative growth effects under relatively modest rates. Most contributions to monetary growth theory, however, have difficulties in explaining such a pattern. It is shown in this paper that this problem can be overcome by establishing a link between monetary instability and the aggregate elasticity of factor substitution. Several microeconomic justifications can be found for a negative influence of inflation on factor substitution. It turns out that in a simple neoclassical monetary growth model this effect is usually strong enough to question the superneutrality benchmark result in the steady state and to dominate all potential positive effects of inflation along the convergence path. (JEL E52, O11, O41)
Keywords: E52; O11; O41; 330